Intuitively visualizing spatial data from biogeographic assessments: A 3-dimensional case study on remotely sensing historic shipwrecks and associated marine life - Paxton, Avery B.; Ebert, Erik F.; Casserley, Tane R.; Taylor, J. Christopher (Frontiers in Climate, 2022)
Biogeographic assessments aim to determine spatial and temporal distributions of organisms and habitats to help inform resource management decisions. In marine systems, rapid technological advances in sensors employed for biogeographic assessments allow scientists to collect unprecedented volumes of data, yet it remains challenging to visually and intuitively convey these sometimes massive spatial or temporal data as actionable information in geographically relevant maps or virtual models. Here, we provide a case study demonstrating an approach to bridge this data visualization gap by displaying coastal ocean data in a 3D, interactive online format. Our case study documents a workflow that provides resource managers, stakeholders, and the general public with a platform for direct exploration of and interaction with 3D data from hydrographically mapping shipwrecks and marine life on the continental shelf of North Carolina, USA. We simultaneously mapped shipwrecks and their associated fish using echosounders. A multibeam echosounder collected high-resolution multibeam bathymetry of the shipwrecks and detected the broad extent of fish schools. A calibrated splitbeam echosounder detected individual fish and fish schools. After processing the echosounder data, we built an interactive, online 3D data visualization web application complemented by multimedia and story text using ESRI geographic information systems. The freely available visual environment, called “Living Shipwrecks 3D,” allows direct engagement with the biogeographic assessment data in a customizable format. We anticipate that additional interactive 3D data applications can be constructed using a similar workflow allowing seamless exploration of complex spatial data used in biogeographic assessments.